Effect of Microbial Community Succession on Tyrosine Metabolism during Soybean Paste Fermentation - JIN Manqin, LUO Dan, WANG Gangtu, LI Yixin, PEI Wei, XUE Wentong (Shipin Kexue)
To find an effective method for eliminating white spots on the surface of soybean paste and enhancing its quality, this study analyzed the relationship between microbial community succession and physicochemical properties and the tyrosine metabolic pathway throughout the entire production cycle of soybean paste. The results showed that the dominant bacteria during the fermentation process were Klebsiella, Bacillus, Tetragenococcus, Pediococcus, Staphylococcus, Enterococcus and Weissiella, and the dominant fungi were Aspergillus, Zygosaccharomyces and Issatchenkia. The microbial community succession was primarily affected by pH, total acidity and amino nitrogen content. The primary functional communities involved in tyrosine metabolism were Enterobacter and Bacillus. Furthermore, in the initial stage of fermentation, Bacillus exhibited a higher potential for tyrosine degradation, whereas Enterobacter demonstrated a significantly greater potential for tyrosine synthesis during the whole fermentation process. These results provide a theoretical basis for reducing the tyrosine content in soybean paste and addressing the issue of white spots and holds practical significance for enhancing the visual quality of soybean paste products.